Investigations of a rabbit (Oryctolagus cuniculus) model of systemic lupus erythematosus (SLE), BAFF and its receptors. - Jiahui Yang (Public Library of Science (PLoS), 2009)
B-cell activation factor belonging to the tumor necrosis factor family (BAFF) is a major contributor to survival of B lymphocytes during development and maturation. A relationship between circulating BAFF levels and disease activity has been reported in patients with the autoimmune disease Systemic Lupus Erythematosus (SLE). Clinical trials targeting BAFF or its receptors are currently in progress. In order to further characterize a rabbit (Oryctolagus cuniculus) model of SLE, we investigated the expression of BAFF and its receptors in non-inbred, pedigreed rabbits derived from breeding and selection based on autoantibody responses. We immunized rabbits related to previous groups that developed autoantibodies and inflammatory responses after immunizations with peptides synthesized on multiple antigen-branched polylysine backbones. Blood and sera collected before immunization and after boosts were used for health monitoring, analyses of serum autoantibody responses by ELISA and immunofluorescence. Peripheral blood mononuclear cells (PBMC) were studied by flow cytometry and were the source of mRNA for quantitative PCR analyses. We hypothesized that BAFF mRNA expression and serum BAFF levels measured indirectly through BAFF receptor binding might increase in autoantibody-producing rabbits. Immunized rabbits developed elevated levels of leucocyte populations, anti-nuclear, anti-dsDNA and other autoantibodies. BR3 mRNA levels in total PBMC decreased and BAFF levels remained low and unchanged in most immunized rabbits. By flow cytometry, percentages of BAFF positive cells decreased. Percentages of transmembrane activator and CAML interactor (TACI) decreased in most rabbits from all the immunized groups. The rabbit is an important model for human autoimmune and infectious diseases, and a high quality draft rabbit genome assembly was recently completed. Human disease models developed in non-inbred pedigreed animals are better able to reflect the complexities of diseases such as SLE with familial patterns of inheritance. Although no consistent pattern of elevated expression of BAFF mRNA or protein was found in the rabbits studied, the data collected and reported here build upon previous data to refine understanding of a rabbit model of SLE.